Macro-determinants of short-term foreign debt in Ghana - William Gabriel Brafu-Insaidoo; Ferdinand Ahiakpor; Fiador Vera Ogeh; Cantah William G. (Cogent Economics & Finance, 2019)
This study tests the validity of the hypothesis that the regulatory and macroeconomic environments and the disparity between domestic and international interest rates are important determinants of short-term foreign debt stock in a developing economy like Ghana. This study employs a time series econometric analysis of annual secondary data covering the period 1970 to 2012. More specifically, the bounds testing approach is used to estimate the impact of potential determinants-identified in the theoretical and empirical literature-on the real stock of short-term foreign debt in Ghana. The study finds that a reduction in regulatory restrictions on external borrowing, a widening of the disparity between domestic and international interest rates, economic growth performance and domestic financial deepening lead to increases in the short-term foreign debt stock in both the long and short run, respectively. The short-term foreign debt stock reduces in response to an increase in trade openness in the short run, and to international debt relief initiatives by multilateral development institutions in the long run.
Keywords: 330; capital accounts liberalization; short-term foreign debt; foreign borrowing